An analysis of the legality of the prosecutorial powers of the Special Anti-Corruption Unit. - Ndebele, Shantel Ellinah (Midlands State University, 2021)
This study examines the role played by prosecutors in the fight against corruption in Zimbabwe. The main objective of the research is to analyse the legality of the Special Anti-Corruption Unit’s power to prosecute corruption matters. The research argues that the Special Anti-Corruption Unit has no legal justification because its powers conflict with those of the National Prosecuting Authority and it also lacks the independence required of prosecutors. To clearly define the role of prosecutors, the study explores the regional and international best practices on the duties and functions of the prosecutors. The study further gives a comparative analysis of the exclusive role of the National Prosecuting Authority in South Africa and the importance of preserving constitutional independence of prosecutors. A desktop research study is used. The key findings are that for any prosecuting authority to be effective, it must be independent, impartial and must carry out its mandate without influence from the executive. The study concludes by giving recommendations on how to remedy the conflict between powers of the Special Anti-Corruption Unit and those of the National Prosecuting Authority.